Persepsi Ibu Hamil Terhadap Program Antenatal Terpadu di Puskesmas Bone Rombo Kabupaten Buton Utara - Hastuti, Wa Ode Sriy; Yuniar, Nani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The maternal mortality rate (MMR) is the main focus in the Sustainable Development Goals (SDGs). According to the World Health Organization (WHO), Indonesia has the highest maternal mortality rate in Southeast Asia and is still far from the global SDGs target. This results in a lack of achievement in Integrated ANC inspections, so that ANC visits are still below the set target. This research aims to explore the implementation of the Integrated ANC program at the Bone Rombo Community Health Center, North Buton Regency in 2023. The method used in this research is qualitative with a phenomenological design, involving 32 informants selected through a purposive sampling technique. The instruments used include interview guidelines and observation sheets. The results of the research show that from an individual perspective, pregnant women's perceptions of the evaluation of the Integrated ANC program at the Bone Rombo Community Health Center are not in accordance with the third edition of 2020 service guidelines. However, the experiences of pregnant women regarding the evaluation of this program are in accordance with these guidelines.